2010
DOI: 10.2522/ptj.20090173
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Clinical Practice Guidelines for Low Back Pain in Physical Therapy: Do Patients Benefit?

Abstract: The results indicate that higher percentages of guideline adherence are related to better improvement of physical functioning and to a lower utilization of care. A proper assessment of the relationship between the process of physical therapy care and outcomes may require a comprehensive set of process indicators to measure guideline adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 37 publications
5
116
0
10
Order By: Relevance
“…A recent study by Rutten et al found that increased adherence by physiotherapists to the Dutch physical therapy and manual therapy guidelines lead to greater improvements in physical functioning and lower utilization of care. 37 Despite this emerging evidence supporting the use of CPG's in the management of LBP, a recent paper by Harman et al documented the prevalence of interventions poorly supported by evidence in the management of subacute LBP by physiotherapists working with injured workers. 38 Using CPGs or the best available evidence in clinical decision making is not compulsory, but the onus is on health care providers to integrate evidence into their clinical decisions whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Rutten et al found that increased adherence by physiotherapists to the Dutch physical therapy and manual therapy guidelines lead to greater improvements in physical functioning and lower utilization of care. 37 Despite this emerging evidence supporting the use of CPG's in the management of LBP, a recent paper by Harman et al documented the prevalence of interventions poorly supported by evidence in the management of subacute LBP by physiotherapists working with injured workers. 38 Using CPGs or the best available evidence in clinical decision making is not compulsory, but the onus is on health care providers to integrate evidence into their clinical decisions whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CPGs in physiotherapy has been shown to contribute to EBP and improve both quality of care and patient outcomes [36,108,109]. This stresses the need to promote and increase guideline use, and to evaluate implementation efforts aiming to do so.…”
Section: Previous Research On Guideline Implementation In Physiotherapymentioning
confidence: 99%
“…Increasing expansion of technology, changes in lifestyle, sedentary life, awkward positions in sitting and standing, etc. weaken body muscles, in particular muscles that support spinal cord leading to various implications for physical and mental health [1].…”
Section: Introductionmentioning
confidence: 99%